Repeated nebulisation of non-viral CFTR gene therapy in patients with cystic fibrosis: a randomised, double-blind, placebo-controlled, phase 2b trial. Issue 9 (September 2015) - Alton, Eric W F W; Armstrong, David K; Ashby, Deborah; Bayfield, Katie J; Bilton, Diana; Bloomfield, Emily V; Boyd, A Christopher; Brand, June; Buchan, Ruaridh; Calcedo, Roberto; Carvelli, Paula; Chan, Mario; et al.
Summary Background Lung delivery of plasmid DNA encoding the CFTR gene complexed with a cationic liposome is a potential treatment option for patients with cystic fibrosis. We aimed to assess the efficacy of non-viral CFTR gene therapy in patients with cystic fibrosis. Methods We did this randomised, double-blind, placebo-controlled, phase 2b trial in two cystic fibrosis centres with patients recruited from 18 sites in the UK. Patients (aged ≥12 years) with a forced expiratory volume in 1 s (FEV1) of 50–90% predicted and any combination of CFTR mutations, were randomly assigned, via a computer-based randomisation system, to receive 5 mL of either nebulised pGM169/GL67A gene–liposome complex or 0·9% saline (placebo) every 28 days (plus or minus 5 days) for 1 year. Randomisation was stratified by % predicted FEV1 (<70 vs ≥70%), age (<18 vs ≥18 years), inclusion in the mechanistic substudy, and dosing site (London or Edinburgh). Participants and investigators were masked to treatment allocation. The primary endpoint was the relative change in % predicted FEV1. The primary analysis was per protocol. This trial is registered with ClinicalTrials.gov, number NCT01621867. Findings Between June 12, 2012, and June 24, 2013, we randomly assigned 140 patients to receive placebo (n=62) or pGM169/GL67A (n=78), of whom 116 (83%) patients comprised the per-protocol population. We noted a significant, albeit modest, treatment effect in the pGM169/GL67A group versus placebo at 12 months' follow-up (3·7%, 95% CI 0·1–7·3; p=0·046). This outcome was associated with a stabilisation of lung function in the pGM169/GL67A group compared with a decline in the placebo group. We recorded no significant difference in treatment-attributable adverse events between groups. Interpretation Monthly application of the pGM169/GL67A gene therapy formulation was associated with a significant, albeit modest, benefit in FEV1 compared with placebo at 1 year, indicating a stabilisation of lung function in the treatment group. Further improvements in efficacy and consistency of response to the current formulation are needed before gene therapy is suitable for clinical care; however, our findings should also encourage the rapid introduction of more potent gene transfer vectors into early phase trials. Funding Medical Research Council/National Institute for Health Research Efficacy and Mechanism Evaluation Programme.